Constructal Hypothesis for Mechanical Deformation - Chatterjee, Atanu (International Journal of Engineering and Technology, 2012)
Mild Steel specimen, when subjected to tensile forces shows considerable plastic deformation before fracture. A cross-section of the fractured specimen has the familiar cup – cone form and shows traces of a three – dimensional parabolic geometry. The morphing of the steel specimen from a volume to a point as a spontaneous, entropy producing or energy dispersing process is analysed using the Constructal law.